Use of airway clearance therapy in children hospitalised with acute lower respiratory tract infections in a South African paediatric hospital - Lieselotte Corten; Brenda M. Morrow (AOSIS, 2020)
Background: Little is known about the prescription, frequency and nature of airway clearance therapy (ACT) in children hospitalised with lower respiratory tract infections (LRTIs). Objectives: To describe the characteristics and outcomes of children hospitalised with LRTIs at a tertiary paediatric hospital in South Africa and to investigate the role and impact of ACT in these children. Method: A retrospective folder review of children hospitalised with LRTI between January and June 2015 was conducted, extracting data on demographic characteristics, health condition, ACT interventions and patient outcomes. Results: A total of 1208 individual cases (median [IQR] age 7.6 (2.8-19.0) months), in 1440 hospitalisations, were included. The majority of children were hospitalised primarily for the management of bronchiolitis. Comorbidities were present in 52.6% of patients during at least one of their hospitalisations. Airway clearance therapy was administered in 5.9% (n = 85) of admissions, most commonly conventional (manual) ACT. Transient oxyhaemoglobin desaturation was reported in six children, and one child developed lobar collapse an hour post-treatment. No other adverse events were reported. The median (IQR) duration of hospitalisation was 2.3 (1.5-5.0) days, and the overall mortality rate was 0.7%. Children hospitalised for presumed nosocomial infections and pneumonia had the longest length of stay, were more likely to receive ACT and had the highest mortality rate. Conclusion: Airway clearance therapy was infrequently used in this population and was more commonly applied in those with nosocomial LRTI and pneumonia. Clinical implications: Although ACT was generally well tolerated, safety has not been ascertained, and oxygen saturation should be carefully monitored during therapy.